Implementasi Prinsip Kehati-Hatian (Prudential Banking Principle) Dalam Penyaluran Kredit Usaha Rakyat (KUR) Pada Bank Rakyat Indonesia Cabang Tasikmalaya - Ernawati, Ninih (Jurnal Hukum In Concreto, 2023)
The banking sector, which has a strategic position as an intermediary institution and supporting the banking system, is a very decisive factor in the adjustment process. In connection with this, it is necessary to improve the national banking system which not only includes efforts to restructure individual banks but also to restructure the banking system as a whole. This research uses the Descriptive-analytical method, namely by describing the prudential principles at Bank Rakyat Indonesia which are described in such a way, then analyzed against lending to provide freedom to the parties who will enter into an agreement. The regulation of the prudential principle in Indonesia is based on Article 2 and Article 29 paragraph (2) of the Banking Law, and implicitly mentions the prudential principle in Article 29 paragraph (3) and (4) of the Banking Law. The prudential principle in granting People's Business Credit (KUR) at Bank Rakyat Indonesia (BRI) KC Tasikmalaya, has applied the prudential principle in granting KUR by using the 5'C principles feasibility analysis (by prioritizing the aspects of character, capacity and collateral analysis) which are assessed through the business income earned each month and the feasibility of collateral provided by prospective debtors.